KATA MAJEMUK DALAM FILM SAVING PRIVATE RYAN OLEH STEVEN SPIELBERG - SAWUWU, HENDRIK SOLEMAN; RANUNTU, GARRYN CHRISTIAN; SIGARLAKI, STEPHANI J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTÂ Compound words consists of addition of stems in which a word is formed by the combination of two independent words. The parts of compound can be free morpheme, derivative word, or another compound. Compound is a lexical unit consisting and semantically as a single word. Compounding is a process of combining of lexical categories: noun, verb, adjective od preposition to create a larger word and the resultant meaning is new or different from its element. This research focuses on compound word of English. The foreign students find many difficulties to use compound words which is usually used by the native speaker of English. Compound words is one of the important parts of English language. This reality encourages the writer to investigate the form of compound words in the movies entitled â€œSaving Private Ryanâ€. The aim of this research is to identify and to analyze the compound words based on their forms and meaning, the descriptive method is used in this research, and the data have been taken from a movie, and analyzed based on the theory of Oâ€™Grady.The result of this research show that compound words can be found in various forms; they are 7 form, 30 compound words, and 5 unfound forms.Â Â Â Â Â Keywords: Morphology, Compound Word, Saving Private Ryan